2018
DOI: 10.7341/20181422
|View full text |Cite
|
Sign up to set email alerts
|

Bricolage and Social Entrepreneurship to Address Emergent Social Needs: A “Deconstructionist” Perspective

Abstract: Social entrepreneurship is one of the most discussed issues in recent management literature. In particular, social entrepreneurship has recently gained the attention of management scholars interested in understanding its sociological and anthropological aspects. This paper focuses on Claude Lévi-Strauss's notion of "bricolage" and the way it can represent a significant opportunity to address emergent social needs. Building on a postmodernist philosophical perspective, namely Jacques Derrida's "deconstructionis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 68 publications
0
23
0
1
Order By: Relevance
“…What do successful entrepreneurs have in common? Such questions may have varied answers, but the common point is that there is no exception to the identification of entrepreneurial psychological capital ability that affects entrepreneurial success (Zollo et al, 2018). In addition to entrepreneurs, innovators have now become the object of strong national support, but compared to the process and the methods of innovation, the government or the enterprise attaches more importance to the results of innovation (Neumeyer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…What do successful entrepreneurs have in common? Such questions may have varied answers, but the common point is that there is no exception to the identification of entrepreneurial psychological capital ability that affects entrepreneurial success (Zollo et al, 2018). In addition to entrepreneurs, innovators have now become the object of strong national support, but compared to the process and the methods of innovation, the government or the enterprise attaches more importance to the results of innovation (Neumeyer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, this process includes a myriad of risks and often ends with deadlock. Empirical studies confirm that just a fraction of innovation activities lead to practical results and suggest that often private sector creativity (Zollo, Rialti, Ciappei, & Boccardi, 2018) and the size of the support by private enterprise is pivotal (Damijan, Kostevc, & Rojec, 2017).…”
Section: Literature Backgroundmentioning
confidence: 96%
“…Despite this rather strong language, the CSR sceptics are not delirious and selfish cormorants/gannets/graspers, because a number of empirical studies revealed the negative impacts of CSR activities and spending by indicating that CSR practices can become a powerful tool in the hand of the top management (MacGregor et al 2020), generate unnecessary costs, cripple financial results (Barnett 2007) and undermine the competitive advantage (Scherer and Palazzo 2011). This leads to a marketing, which undermines the strength of the information about inventiveness for stakeholders (Roszkowska-Menkes 2017) and about the creation and bringing of values to stakeholders (Zollo et al 2018). In contrast, such type of marketing is founded upon the conviction about the almost inevitable communication noise, inducement to information ignorance and resultant confusion of stakeholders, in particular consumers (Chauhan and Sagar 2021).…”
Section: Theoretical Background-the Carroll's Csr Pyramid Temple Believers and Heretics Before And During The Covid-19 Eramentioning
confidence: 99%